Characteristic Features of the Use of Information and Psychological Confrontation in the Middle East - Golubenko Alexey Yurievich (Genius Journals, 2022)
This article discusses the characteristic features of the US information and psychological confrontation in Iraq and Russia in Syria, reflected in the conceptual and doctrinal documents during these armed conflicts.
Keywords: Information; psychological; operations; conflict